Hubungan Kualitas Menu Terhadap Status Gizi Remaja Di Pondok Pesantren Syafa'aturrasul ,Taluk Kuantan 2020 - Andalia Roza; Putri Wulandini; Arrasidah Nailul Hasanah (LPPM Universitas Abdurrab, 2021)
Nutritional status is the state of the body as a result of food consumption and use of nutrients nutritional status can also be interpreted as a physical sign caused by a balance between income and expenditure through nutrition through certain variables, namely indicators. The quality of the menu is one of the main things besides service and kitchen cleanliness that must be maintained properly. The purpose of this study is to find out whether there is a relationship between the quality of the menu to the nutritional status of adolescents in the Pondok Ampar Syafa'aturrasul Batu Ampar, Beringin Taluk Kuantan. This type of research is correlated with cross sectional research design. The population in this study were all adolescents in Syafa'aturrasul Islamic Boarding School with a total of 800 inhabitants. The sample used was 267 students. The sampling technique is to use cluster sampling technique. The research instrument used observation sheets. The data obtained was processed by univariate and bivariate data analysis. The results obtained p value 0.27 means p value> 0.05, it can be concluded that there is no significant relationship between the quality of the menu on the nutritional status of adolescents in the Gyafa'aturrasul Islamic boarding school in Beruk, Taluk Kuantan. It is expected that the cottage together with parents work together to prevent and provide health education on good nutritional status for adolescence.